Dihydropyriculol produced by Pyricularia oryzae inhibits the growth of Streptomyces griseus. Issue 5 (10th February 2021) - Furuyama, Yuuki; Motoyama, Takayuki; Nogawa, Toshihiko; Kamakura, Takashi; Osada, Hiroyuki
ABSTRACT: Dihydropyriculol is a major secondary metabolite of Pyricularia oryzae . However, the biological activity of dihydropyriculol has not been reported. Here, we showed that dihydropyriculol has inhibitory activity against Streptomyces griseus. Localization analysis of dihydropyriculol revealed that dihydropyriculol could reach to S. griseus under confrontation culture. These results suggest that dihydropyriculol can be used as a chemical weapon against S. griseu s.